Remote Control Implementation of the Hydraulic Turbine Governor on the Test Field - Stevanović, Jovan; Kvaščev, Goran; Dragićević, Miroslav; Pavlović, Jelena (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
This paper presents the enhancement of the turbine governor test field of a hydraulic turbine through the implementation of a modern SCADA system based on an integrated PLC web server and OPC UA communication with a Simulink environment simulator and turbine governor. The system enables realistic simulation of turbine governor operation under laboratory conditions, with the capability of remote monitoring and parameter adjustment via a standard web browser. Within the research, a web server SCADA system was developed on the Siemens S7-1500 PLC, connecting the physical controller and the simulation model into a unified hardware-in-the-loop (HIL) environment. The obtained results demonstrate a significant improvement in the flexibility, transparency, and efficiency of the turbine governor testing process.
Keywords: SCADA; PLC; web server; Siemens S7-1500; Simulink; turbine governor